Improving Students’ Speaking Competence Through Vlog Media At The First Year Of Madrasah Aliyah Negeri 3 Padang Panjang - Yuni, Rafika; Hendrita, Rini; Syam, Erlinda (Yayasan Lembaga Studi Makwa, 2023)
This research aimed to discuss how vlog can improve students’ speaking competence. This research model is a pre-experimental research in one design group which is devided into three stages, namely pre-tes, treatment,post-test in the learning process. The sample of this reseaech was class X E2 consisting 15 students at MAN 3 Padangpanjang in academic year 2023/2024. Instruments for collecting data were pre-test and post-test through students’ performance with test and measured using an assesment rubric. The success criteria are determind on three indicators, namely grammar, pronounciation and fluency. The result of this research showed that the use of video blog (vlog) media in teaching speaking improved the students’ speaking competence well. It could be seen on the students’ mean score for each test that showed the post-test got higher after doing treatment by using vlog media than pre-test before doing treatment by using vlog media, that is 75 for post-test and 37 for pre-test. And it can be seen from the result of the hypothesis where t-count > t-table (21,11>2,145 ). The alternative hypothesis (Ha) is accepted while the null hypothesis (Ho) is rejected. Therefore, it could be concluded that there is any improvement of students’ speaking competence at the first year of MAN 3 Padangpanjang by using video blog (vlog). Abstrak Penelitian ini bertujuan untuk meneliti bagaiman vlog bisa meningkatkan kemampuan berbicara siswa. Model penelitian ini adalah penelitian pra eksperimental dalam satu kelompok desain yang dibagi kedalam tiga tahap yaitu pre-test, treatment, dan post-test di dalam proses pembelajaran. Sample dari penelitian ini adalah kelas X E2 yang terdiri dari 15 siswa di MAN 3 Padangpanjang. Instrumen untuk mengumpulkan data adalah pre-test and post-test melalui kinerja siswa dengan tes lisan dan diukur dengan menggunakan rubrik penilaian. Kriteria keberhasilan ditentukan oleh tiga indikator, yaitu grammar, pronounciation dan fluency. Hasil penelitian ini menunjukkan bahwa penggunaan media video blog (vlog) dalam pengajaran berbicara meningkatkan kompetensi berbicara siswa dengan baik. Hal ini dapat dilihat pada nilai rata-rata siswa untuk setiap tes yang menunjukkan post-test lebih tinggi setelah dilakukan perlakuan dengan menggunakan vlog media daripada pre-test sebelum melakukan perlakuan dengan menggunakan vlog media, yaitu 75 untuk post-test dan 37 untuk post-test. Dan dapat dilihat dari hasil hipotesis dimana t-hitung > t-tabel (21,11>2.145 ). Hipotesis alternatif (Ha) diterima sedangkan hipotesis nol (Ho) ditolak. Oleh karena itu, dapat disimpulkan bahwa terdapat peningkatan kompetensi berbicara siswa di tahun pertama MAN 3 Padang Panjang dengan menggunakan video blog (vlog).